2023
DOI: 10.1186/s40795-023-00701-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with stunting: gut inflammation and child and maternal-related contributors among under-five children in Hawassa City, Sidama Region, Ethiopia

Abstract: Background Under-nutrition remains a major global public health challenge, particularly among children under the age of five. Among the manifestations of under-nutrition, stunting accounts for the larger proportion, which is associated with multiple factors. In Ethiopia, however, the link between intestinal inflammation and childhood stunting was not well investigated. Therefore, the present study aimed to determine the association between gut inflammation and childhood stunting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Research has found that there is a significant relationship between household waste and the incidence of stunting. (Lefebo et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that there is a significant relationship between household waste and the incidence of stunting. (Lefebo et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Giving Moringa extract to pregnant women provides an abundant supply of micronutrients including Fe, Vitamin A, Vitamin C, and selenium during pregnancy. Therefore, mothers who consume Moringa are filled with micronutrients, such as Fe in Moringa extract which increases hemoglobin in pregnant women and prevents DNA damage due to oxidative stress (Lefebo et al, 2023).…”
Section: Discussionmentioning
confidence: 99%